Purkinje cell activity changes in cerebellar subregions during fear conditioning - Pakusch, Johanna; Nair, Tejas; Grosch, Thomas; Mark, Melanie D. (Frontiers in Behavioral Neuroscience, 2025)
The cerebellum has been recently implicated in modulating fear behavior. The collective activity of Purkinje cells (PCs) across cerebellar regions during fear conditioning remains unexplored. In this brief report we implemented the targeted recombination in active populations (TRAP) system to investigate intracerebellar PC activity during cue dependent fear conditioning in mice. Purkinje cell activity was reduced in areas previously implicated in controlling aversive emotions, which included cerebellar subregions Crus I and II and lobule VI with more pronounced changes in the left cerebellar hemisphere and increases in the lobule VIII subareas in the right hemisphere. Additional PC activity increases related to motor function were observed from the right hemispheric subregions of the paraflocculus and decreases in the left copula pyramidis. These findings underscore the importance of examining the contribution of cerebellar subregions in the context of fear learning, highlighting the potential lateralization of cerebellar fear emotions.